Lung cancer diagnosed following emergency admission: a mixed methods study protocol to improve understanding of patients’ characteristics, needs, experiences and outcomes - Wilcock, Andrew; Crosby, Vincent; Freer, Sarah; Freemantle, Alison; Caswell, Glenys; Seymour, Jane (BioMed Central, 2013)
Background Lung cancer is the leading cause of death from cancer in England. About 40% of patients with lung cancer are diagnosed following an emergency admission (DFEA) to hospital. DFEA is more common in women, and more likely with increasing age and deprivation. Most have advanced disease and survival is poor, but little else is known about this group. The aim of this study is to obtain a detailed understanding of the characteristics, needs, experiences and outcomes of this group.